(untitled) (Journal of Oriental Studies, 2018)
Toponymy is a part of onomastics which researches the origin, names of the geographical names, their meanings, development of the structure,the current position of their location, their grammatical, phonetic form,writing and transmissions to a different language. It comes from the Greek word «topos», the place, the earth, «onoma» - consists of two words, i.e. means the name of the locality. The toponyms that are explored in onomastics are linguistic units that exist for many centuries along with the ethnos. Also, the names of localities - is an indicator of our national linguistic wealth, culture, traditions and the knowledge of the world around us. In this article, information was given on the studies conducted by Turkish scientists on the names of localities in the Turkish language. And also, in this article such scientists as H. Nihal, A. Naji, H. Eren, O. Bashkan, T. Baikara, T. Gulensoy etc. under the initiative of F. Koprul, were considered whose works served as a good source for those who studied toponyms in Turkish language.